2002
DOI: 10.1074/jbc.m209566200
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Binding and Histone Modifications on the Integrated Proviral Promoter in Human T-cell Leukemia Virus-I-infected T-cells

Abstract: The human T-cell leukemia virus (HTLV-I)-encodedTax protein is a potent transcriptional activator that stimulates expression of the integrated provirus. Biochemical studies indicate that Tax, together with cellular transcription factors, interacts with viral cAMP-response element enhancer elements to recruit the pleiotropic coactivators CREB-binding protein and p300. Histone acetylation by these coactivators has been shown to play a major role in activating HTLV-I transcription from chromatin templates in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
82
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 64 publications
(65 reference statements)
4
82
0
Order By: Relevance
“…expression of the HTLV-I promoter (42,43), with the viral CRE sites being the functional c-Jun-responsive targets in the promoter (42). In light of our results, HBZ should be able to down-regulate viral transcription in the presence of c-Jun.…”
Section: Transactivation Of the Htlv-i Promoter By C-jun Is Inhibitedmentioning
confidence: 92%
See 1 more Smart Citation
“…expression of the HTLV-I promoter (42,43), with the viral CRE sites being the functional c-Jun-responsive targets in the promoter (42). In light of our results, HBZ should be able to down-regulate viral transcription in the presence of c-Jun.…”
Section: Transactivation Of the Htlv-i Promoter By C-jun Is Inhibitedmentioning
confidence: 92%
“…Then, the promoter-bound Tax molecule recruits the transcriptional coactivator CREB-binding protein, which is involved in the acetylation of the core histone tails (40,41). AP-1 is also able to transactivate the HTLV-I promoter in vivo (42,43). However, no direct interactions between the AP-1 factors and Tax have been characterized, suggesting that AP-1 is obviously involved in basal transcription of the HTLV-I genome.…”
mentioning
confidence: 99%
“…Among proteins that carry intrinsic histone acetyltransferase activity, the coactivators CBP/p300 have been shown to have an essential role in HTLV-1 transcriptional activation. Our laboratories, as well as others, detected CBP/p300 at the integrated HTLV-1 promoter in T-cells expressing high levels of Tax (23,24). This finding is consistent with several previous studies showing that Tax directly facilitates the recruitment of CBP/p300 to the HTLV-1 promoter (16,17,25,26).…”
mentioning
confidence: 99%
“…Using chromatin assembled with core histones lacking their amino-terminal tails and using specific inhibitors of CBP/p300, we have found that CBP/p300 participate in critical chromatin-specific, histone tail-independent acetylation events during transcriptional activation by Tax (28). These data suggest that, in addition to the core histone tails, another target of acetylation by p300 functions in mediating strong Tax transactivation in a chromatin environment.In previous studies we have examined transcription factor binding and histone modifications at the viral promoter in Tax-expressing, HTLV-1-infected cells (23,29). In this study, we sought to better define the epigenetic changes that occur during Tax-dependent activation of HTLV-1 LTR-directed transcription in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation